The Role of Limbal Epithelial Stem Cells in Regulating Corneal (Lymph)angiogenic Privilege and the Micromilieu of the Limbal Niche following UV Exposure - M. Notara; A. Lentzsch; M. Coroneo; C. Cursiefen (Hindawi Limited, 2018)
The cornea is a clear structure, void of blood, and lymphatic vessels, functioning as our window to the world. Limbal epithelial stem cells, occupying the area between avascular cornea and vascularized conjunctiva, have been implicated in tissue border maintenance, preventing conjunctivalisation and propagation of blood and lymphatic vessels into the cornea. Defects in limbal epithelial stem cells are linked to corneal neovascularisation, including lymphangiogenesis, chronic inflammation, conjunctivalisation, epithelial abnormalities including the presence of goblet cells, breaks in Bowman's membrane, persistent epithelial defects and ulceration, ocular surface squamous neoplasia, lipid keratopathy, pain, discomfort, and compromised vision. It has been postulated that pterygium is an example of focal limbal deficiency. Previous reports showing changes occurring in limbal epithelium during pterygium pathogenesis suggest that there is a link to stem cell damage. In this light, pterygium can serve as a model disease of UV-induced stem cell damage also characterised by corneal blood and lymphangiogenesis. This review focuses on the role of corneal and limbal epithelial cells and the stem cell niche in maintaining corneal avascularity and corneal immune privilege and how this may be deregulated following UV exposure. We present an overview of the PUBMED literature in the field as well as recent work from our laboratories.